Persepsi Pegawai Terhadap Praktik Penindasan Di Tempat Kerja: Kasus Dugaan Phk Sepihak Di Alfamart Gorontalo Dan Pengaruhnya Terhdap Etos Kerja - Harold, Rudy (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to understand employees’ perceptions of workplace oppression in the case of alleged unilateral termination of employment (PHK) at Alfamart Gorontalo, and to analyze how such practices affect employee work ethic. The unilateral termination phenomenon reflects an imbalance of power relations between the company and its workers, creating suspicions of arbitrary actions that potentially suppress employees’ positions. This research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. Informants were selected using purposive sampling, focusing on employees who were considered relevantto the incident. Data analysis refers to the Interactive Model of Miles, Huberman, and Saldana, which consists of data collection, data condensation, data display, and conclusion drawing. The findings indicate that unilateral termination is perceived by employees as a form of structural oppression, as it was carried out without transparent communication, without providing the opportunity for self-defense, and resulted in psychological pressure and uncertainty among workers. The impact of such practices is reflected in decreased motivation and work ethic among employees who feel that their rights are not respected. This study highlights the importance of implementing principles of fairness, transparency, and labor protection to prevent the emergence of oppressive practices in the workplace.